Thermal ideality factor of hydrogenated amorphous silicon p-i-n solar cells - Kind, R. (2011)
The performance of hydrogenated amorphous silicon (a-Si:H) p-i-n solar cells is limited, as they contain a relatively high concentration of defects. The dark current voltage (JV) characteristics at low forward voltages of these devices are dominated by recombination processes. The recombination rate depends on the concentration of active recombination centers and the recombination efficacy of each of these centers. The first factor causes the ideality factor of the devices to be non-integer and to vary with voltage. The temperature dependence of the dark current can be expressed by its activation energy. For microcrystalline silicon solar cells the activation energy varies with voltage with a so-called thermal ideality factor of 2. This value was derived for devices with a spatially uniform defect distribution and reflects the recombination efficacy. Here we present results of a thickness series of a-Si:H p-i-n solar cells. We have matched the experimental curves with computer simulations, and show that the voltage-dependent ideality factor curve can be used to extract information on the cross sections for electron and hole capture. Also, the activation energy is used as a measure for the mobility gap, resulting in a mobility gap for a-Si:H of 1.69 eV. We find a thermal ideality factor close to 2 for all samples. This is explained with a theoretical derivation, followed by a comparison between the internal electric field strength and the spatial variation of the defect density in the intrinsic layer. The thermal ideality factor is shown to be insensitive to the defect distribution and the recombination profile in the device. It is, therefore, an appropriate parameter to characterize a-Si:H p-i-n devices, providing direct insight on the recombination efficacy.